Obesity and abdominal aortic aneurysm. Issue 3 (30th November 2012) - Stackelberg, O.; Björck, M.; Sadr‐Azodi, O.; Larsson, S. C.; Orsini, N.; Wolk, A.
Abstract Background: The relationship between obesity and abdominal aortic aneurysm (AAA) is unclear. An observational cohort study was undertaken to examine the associations between waist circumference as a measure of abdominal adiposity, and between body mass index (BMI) as a measure of total adiposity, and risk of AAA. Methods: Data were used from the population‐based Swedish Mammography Cohort and the Cohort of Swedish Men, involving 63 655 men and women, aged 46–84 years. Between 1998 and 2009, 597 patients with incident AAA defined by relevant clinical events were identified by linkage to the Swedish Inpatient Register and the Swedish Vascular Registry. Cox proportional hazards models were used to estimate relative risks (RRs) with 95 per cent confidence intervals. Results: In multivariable analysis, individuals with an increased waist circumference had a 30 per cent higher risk of AAA (RR 1·30, 95 per cent confidence interval 1·05 to 1·60) compared with those with a normal waist circumference. The risk of AAA increased by 15 per cent (RR 1·15, 1·05 to 1·26) per 5‐cm increment of waist circumference up to the level 100 cm for men and 88 cm for women. There was no association between BMI and risk of AAA. Conclusion: Abdominal, but not total, adiposity was associated with an increased risk of incident AAA. A threshold was observed at a waist circumference of 100 cm for men and 88 cm for women. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.